PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DENGAN MODEL OPEN ENDED DI SEKOLAH DASAR - Della Afriana Tasya; Rusdial Marta; Mufarizuddin; Fadhilaturrahmi; Iis Aprinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve elementary school students' mathematical creative thinking skills through the implementation of the Open-Ended learning model. This study used a Classroom Action Research (CAR) approach, implemented in two cycles, each consisting of two meetings. Each cycle included planning, implementation, observation, and reflection, with a focus on developing open-ended modules, open-ended questions, and observation instruments for teacher and student activities. The results showed an increase in students' creative thinking skills, from an average of 58.33 in the first meeting of cycle I to 84,08 in the second meeting of cycle II, with the percentage of students completing the task increasing from 50% to 83,33%. These results confirm that the implementation of the Open-Ended learning model is effective in improving students' mathematical creative thinking skills. Based on these findings, it is recommended that teachers continue to implement the Open-Ended model, provide a variety of challenging questions, and facilitate group discussions to support the optimal development of student creativity.